Religiusitas dan Kepercayaan Masyarakat Bugis- Makassar - Mustaqim Pabbajah (Al-Ulum, 2012)
This article explores the old beliefs of Bugis and Makassar peoples. The old beliefs which still exist and are preserved within community until nowadays. In the concept of god, for example, the terms of â€œDewata SeuwwaEâ€ (Bugis) and â€œTau ri Aâ€™ranaâ€ (Makaasar) still can be heard and believed. In the daily lifes, the influence of local beliefs cover rituals such â€œmappangre galungâ€ (farmer) and â€œmaccera tasiâ€ (fishermen) still conducted in the community. This article also evaluates the old beliefs of South Sulawesi peoples, both before and after the coming of Islam. Also these religionsâ€™ influences in the daily lives are highlighted. A dynamic dialogue between the local religions and Islam becomes the core of this paper.